2019
DOI: 10.1007/s40544-019-0294-2
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion-tribological property relationship in mineral oils containing 2D layered α-zirconium phosphate nanoplatelets

Abstract: Inorganic nanomaterials exhibit superior friction-reduction and anti-wear properties in oils. In this study, 2D layered -zirconium phosphate (-ZrP) nanosheets intercalated with different amines have been synthesized to study their dispersion stabilities in lubricating oil and tribological applications. The intercalated amines should be sufficiently long and lipophilic to provide stabilization to -ZrP nanosheets in mineral oil. The results of tribological tests illustrate that with the addition of well-dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Similarly, the Raman signals of the exfoliated h-BN and WS 2 are found on the worn surfaces. These results demonstrate that the exfoliated nanosheets can be filled into the groove of the worn surface in ball-milling. Therefore, it can be concluded that ball-milling plays a key role in the structural evolution of bulk layered materials, and the coefficient could reflect the structural change in bulk layered materials at the friction interface to some extent. That is to say, the originally integrated structure makes a great contribution to the better lubrication properties.…”
Section: Resultsmentioning
confidence: 81%
“…Similarly, the Raman signals of the exfoliated h-BN and WS 2 are found on the worn surfaces. These results demonstrate that the exfoliated nanosheets can be filled into the groove of the worn surface in ball-milling. Therefore, it can be concluded that ball-milling plays a key role in the structural evolution of bulk layered materials, and the coefficient could reflect the structural change in bulk layered materials at the friction interface to some extent. That is to say, the originally integrated structure makes a great contribution to the better lubrication properties.…”
Section: Resultsmentioning
confidence: 81%
“…α‐ZrP has a good anti‐wear performance, friction reduction, and load‐carrying capacity as a solid lubricating additive 55,56 . Figure 12 shows the typical frictional curves of the four coatings versus time.…”
Section: Resultsmentioning
confidence: 99%
“…α-ZrP has a good anti-wear performance, friction reduction, and load-carrying capacity as a solid lubricating additive. 55,56 Figure 12 shows the typical frictional curves of the four coatings versus time. The COF of composites with no coating treatment was high and exhibited large fluctuation.…”
Section: Tribological Experimentsmentioning
confidence: 99%
“…The interaction between a fluid in movement and a solid generates considerable energy losses due to resistance to flow, also called drag. Minimizing drag losses is beneficial for a multitude of industries, such as the naval and aeronautics industries [1][2][3][4][5][6]. Still, in the 1940s, it was discovered that the addition of small amounts of soluble polymers with a high molecular weight was affected by flow resistance without affecting the viscosity or density of the fluid in turbulence [7].…”
Section: Introductionmentioning
confidence: 99%